Hierarchical Structuring of Fibrous Materials: Toward Tailored Properties for High-Performance Textile Products - Mahadasa, Ravikiran (Engineering International, 2021)
This study aims to determine whether fiber materials with hierarchical organization can improve the qualities of textile goods for high-performance uses. The primary goals are to examine functionalization strategies, identify future possibilities in textile engineering, investigate hierarchical structuring methodologies, and analyze hierarchically structured textiles’ mechanical and thermal properties. An extensive examination of extant literature and secondary data sources is carried out to examine the approaches, uses, and difficulties related to hierarchical organization. Important discoveries emphasize how hierarchically organized fabrics have improved mechanical strength, thermal behavior, and functional qualities. The discussion of policy implications follows, focusing on the role of industry cooperation, workforce development, sustainability programs, research funding, and industrial collaboration in improving hierarchically structured textiles. The study’s findings highlight the revolutionary potential of fibrous materials’ hierarchical organization for promoting sustainability and innovation in the textile sector.